Globalization, re-discovery of the Malay 'local,' and popular TV fiction through audience narratives - Mohd Muzhafar Idrus; Hashim R.S.; Raihanah M.M. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by WOS/Scopus